2017
DOI: 10.1016/j.molcel.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide Analysis of Roles for tRNA Modifications in Translational Regulation

Abstract: SUMMARY Covalent nucleotide modifications in noncoding RNAs affect a plethora of biological processes, and new functions continue to be discovered even for well-known modifying enzymes. To systematically compare the functions of a large set of ncRNA modifications in gene regulation, we carried out ribosome profiling in budding yeast to characterize 57 nonessential genes involved in tRNA modification. Deletion mutants exhibited a range of translational phenotypes, with enzymes known to modify anticodons, or non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
163
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(189 citation statements)
references
References 65 publications
(94 reference statements)
17
163
0
Order By: Relevance
“…In our Q-free cell culture system and mouse model, dysregulation of translation resulted in the accumulation of misfolded proteins and aggregates that trigger the activation of ER stress and the UPR. This mechanism is in agreement with the phenotypes recently described in mouse and yeast that lack certain modifications at the wobble position (Laguesse et al, 2015;Chou et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our Q-free cell culture system and mouse model, dysregulation of translation resulted in the accumulation of misfolded proteins and aggregates that trigger the activation of ER stress and the UPR. This mechanism is in agreement with the phenotypes recently described in mouse and yeast that lack certain modifications at the wobble position (Laguesse et al, 2015;Chou et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In particular, position 34 is subject to various modifications (Agris et al , ), depending on the associated tRNA isoacceptor and the organism (Grosjean et al , ; El Yacoubi et al , ). Some of these modifications have been shown to be important for the fine‐tuning of protein translation and for the maintenance of proteome integrity in yeast and in C. elegans (Rezgui et al , ; Zinshteyn & Gilbert, ; Nedialkova & Leidel, ; Chou et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, many RNA modification systems appear not to be essential for life since organisms with mutations in the responsible activities are viable and fertile. However, combining different RNA modification system mutations or exposing particular RNA modification system mutants to non‐standard laboratory conditions (i.e., stress) caused observable phenotypes indicating that the biological function of many RNA modifications has to be sought in the response to environmental insults . Indeed, recent research showed that RNA modification patterns can change, especially during the response to particular stresses resulting, for instance, in the reprogramming of protein translation .…”
Section: Rna Modifications: Potential For Dynamic Regulation Of Rna Pmentioning
confidence: 99%
“…The m2,2G modification could also play a role in proper tRNA interaction with the ribosome to ensure efficient translation. Indeed, studies in yeast S. cerevisiae have found that Trm1 deletion mutants display alterations in ribosome profiles indicative of translation aberrations (Chou, Donnard, Gustafsson, Garber, & Rando, 2017). Moreover, studies in human cells have found that global translation is reduced upon ablation of TRMT1 (Dewe et al, 2017).…”
mentioning
confidence: 99%